2012
DOI: 10.1016/j.nlm.2012.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Developmental effects of acute, chronic, and withdrawal from chronic nicotine on fear conditioning

Abstract: Pre-adolescence and adolescence are developmental periods associated with increased vulnerability for tobacco addiction, and exposure to tobacco during these periods may lead to long-lasting changes in behavioral and neuronal plasticity. The present study examined the short- and long-term effects of nicotine and nicotine withdrawal on fear conditioning in pre-adolescent, adolescent, and adult mice, and potential underlying substrates that may mediate the developmental effects of nicotine, such as changes in ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
134
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 77 publications
(146 citation statements)
references
References 86 publications
(113 reference statements)
10
134
1
1
Order By: Relevance
“…Using different protocols of nicotine administration and testing, some found clear impairments in learning and memory (Sorenson et al , 1991; Vaglenova et al , 2004; Yanai et al , 1992; Portugal et al , 2012), whereas others reported no nicotine effects (Cutler et al , 1996; Huang et al , 2007), only subtle impairments (Levin et al , 1993), or only dose- or sex-specific impairments (Ankarberg et al , 2001; Eppolito and Smith, 2006). Combined, this body of work demonstrates that the effects of nicotine exposure during development are sensitive to a combination of factors including sex, dose and timing of exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using different protocols of nicotine administration and testing, some found clear impairments in learning and memory (Sorenson et al , 1991; Vaglenova et al , 2004; Yanai et al , 1992; Portugal et al , 2012), whereas others reported no nicotine effects (Cutler et al , 1996; Huang et al , 2007), only subtle impairments (Levin et al , 1993), or only dose- or sex-specific impairments (Ankarberg et al , 2001; Eppolito and Smith, 2006). Combined, this body of work demonstrates that the effects of nicotine exposure during development are sensitive to a combination of factors including sex, dose and timing of exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Cigarette smoke has been shown to contain more than 4,000 chemicals, but among these nicotine is thought to be the primary neuroteratogen (Pauly and Slotkin, 2008). Indeed, several studies using rodent models of perinatal nicotine treatment have demonstrated that exposure to the drug during early development causes long-lasting deficits in learning and memory (Ankarberg et al , 2001; Eppolito and Smith, 2006; Sorenson et al , 1991; Vaglenova et al , 2004; Yanai et al , 1992; Portugal et al , 2012). However, the outstanding question in the field remains which cellular and molecular changes induced by nicotine underlie this cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%
“…32,33 Hippocampi from BDNF Val/Val and BDNF Met/Met mice treated with either saline, chronic nicotine (18 mg kg −1 day −1 ) or undergoing 24-hour withdrawal was homogenized and lysed in 1% triton X-100 (Sigma), 1% nonidet P-40 (Roche, Indianapolis, IN) in Tris-buffered saline pH 7.4 with protease inhibitor cocktail (Sigma). Protein concentration was quantified by Bradford (Bio-Rad, Hercules, CA).…”
Section: Western Blotmentioning
confidence: 99%
“…Studies with rodents have shown that withdrawal from chronic nicotine impairs hippocampus-dependent learning (Davis et al ., 2005; Andre et al ., 2008; Portugal and Gould, 2009; Kenney et al ., 2011; Portugal et al ., 2012a, 2012b). Withdrawal from chronic nicotine selectively disrupts contextual, but not cued, fear conditioning (Davis et al ., 2005), a paradigm that approximates important aspects of declarative memory in humans (Kenney and Gould, 2008), whereas acute nicotine enhances this hippocampus-specific learning and memory paradigm (Gould and Wehner, 1999).…”
Section: Introductionmentioning
confidence: 99%